Evaluasi Implementasi E-Government pada Sistem Layanan Kesehatan Digital: Studi pada Aplikasi JakSehat - Hanjani, Antania; Arifianti , Dwi Lina; Febrinaharnum , Humaira; Anitasari , Yuli (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
Since the COVID-19 pandemic, the digital healthcare system has been a prominent element of e-government agendas. JakSehat emerged to implement e-government in Indonesia's health service system. This study aims to evaluate the adaption of e-government services on JakSehat, using digital service evaluation criteria from Alshawi & Alalwany (2010), namely technical, economic, and social issues. The evaluation is significant due to the enormous investment put in by governments to deliver the best public services. This research used a digital qualitative approach to collect data from the Google Play Store. The data was analyzed using a word cloud to map and assess the evaluation criteria. The results show that digitalization in the JakSehat application has yet to provide effectiveness and efficiency in healthcare services from the public perspective.